Cybernetyczny aspekt przetwarzania informacji - Zych, Jan (My University, 2003)
PL W artykule wyeksponowano dominującą rolę informacji na współczesnym polu walki. Poczyniono próbę opisania skutków zwiększania się roli informacji. Z perspektywy cybernetyka opisano proces analizy informacji oraz porównano procesy przetwarzania informacji w układach biologicznych i technicznych. Przedstawiono i skomentowano kilkadziesiąt definicji pojęcia informacja.

EN The article points to the fact of dominating role of information in all the processes identified in the battlefield. There has been made an attempt to verbalise the effects of this phenomenon. It was described on the elementary level, and the process of information analysis was compared in both technical and biological systems. There are given several tens of definitions of the term information and they have been commented on.
Keywords: cybernetyka; informacja; przestrzeń informacyjna; techniczne systemy komputerowe; biologiczne systemy komputerowe; Demon Laplace’a